Promissory Passiflora L. species (Passifloraceae) for tolerance to water-salt stress (2020)
The aim of this study was to determine tolerance to water and salt stress in four cultivated Passiflora L. species. Eleven accessions of four Passiflora species of commercial interest from different plantations were evaluated. The experiment design used sub-split plots, where the plot was the percentage of water saturation in relation to the requirements of the crop (33 and 100%). The subplot was established with the saturation levels of salt (sodium chloride reactive level - 99.9% purity) (EC: 1.5 and 5.5 dS m-1) with the 11 accessions in a completely randomized array with five replications, where the experiment unit was one plant. The results showed that accessions m11, m13 (P. edulis f. flavicarpa) and m15 (P. tarminiana) were tolerant to salinity and drought; accessions m2 (P. edulis f. edulis), m12 and m14 (P. edulis f. flavicarpa) were moderately tolerant. These observations provided a basis for future studies on drought tolerance in Passiflora, which must be followed up with field evaluations.